Analysis of Correlation of Induced Frequency and Cream Skimming Efficiency through Ultrasonic Technology - Arjun, Asogan; Norazlianie, Sazali; Wan Sharuzi, Wan Harun; Devarajan, Ramasamy; Kumaran, Kadirgama (Semarak Ilmu Publishing, 2023)
Ultrasonic cream separator is a very new technology especially in the dairy industry. Ultrasonic separator machine is an eco-friendly technology that could boost the separation process and it could act as supplement to heat-based technology. However, ultrasonic separators are well developed in other industries such as sludge separation, emulsion breaking, de-oiling and sewage disposal. This technology has been implemented in the food industries recently too. The primary function of an ultrasonic cream separator machine is to separate the milk into two products i.e., cream, and skimmed milk. It is an instantaneous process which saves up workload, manpower, time, and cost. This machine intends to coagulate the fat particles with one another once a certain frequency is induced in the milk. Cream, which is lighter molecule will coagulate and float, whereas the heavier molecules of milk such as protein and minerals will sink. Upon separation, the fat molecules can be scooped out or separated through flushing from below. This machine is at a very agile stage that leads to inefficient cream skimming which leads to fluctuation of fat particles coagulation that leads to inefficient cream skimming. The intention of this study is to evaluate the factors that have a direct relationship with low performance of cream skimming via ultrasonic cream separation and come up with an ideal possible solution to enhance the process of cream separation.